Environmental Degradation and Economic Growth in African Low-Income Economies - Kehinde Kabir Agbatogun; Adenuga Fabian Adekoya; Adekunle Ademayowa Adebayo; Mabayoje Albert Sennuga; Adeniyi Marcus Oresanwo (Jurnal Ekonomi dan Studi Pembangunan, 2025)
The study investigated the validity of the environmental Kuznets curve hypothesis regarding the relationship between economic growth and environmental sustainability in low-income African economies, emphasising the impact of financial system development on the pace of urbanisation, utilising data from the World Development Indicators, and employing panel ARDL-AMG techniques. The unit root tests indicate that the variables have a different order of integration. The cross-sectional dependency test, on the other hand, confirmed that the sections are dependent on each other across time. The cointegration test showed a long-term relationship across the whole model. This proved that the second-generation panel unit root test worked, which in turn confirmed what the first-generation test had found. After using the AMG method with a mixed integration order and taking into account the cross-sectional dependence issue, the results indicated that the environmental Kuznets curve was supported by the significant positive and negative GDP per capita and GDP per capita squared coefficients. This evidence points to a nonlinear, inverted U-shaped relationship between economic growth and environmental sustainability. In low-income African economies, urbanisation and financial development have the least positive and negative effects, respectively.